2001
DOI: 10.1136/bmj.323.7316.784
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictors of high quality care in English general practice: observational study

Abstract: Objectives To assess variation in the quality of care in general practice and identify factors associated with high quality care. Design Observational study. Setting Stratified random sample of 60 general practices in six areas of England. Outcome measures Quality of management of chronic disease (angina, asthma in adults, and type 2 diabetes) and preventive care (rates of uptake for immunisation and cervical smear), access to care, continuity of care, and interpersonal care (general practice assessment survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
270
7
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(296 citation statements)
references
References 25 publications
12
270
7
7
Order By: Relevance
“…[14][15][16] Compared with people living in the community, those living in care homes receive poorer care for conditions like heart disease and diabetes, and potentially harmful medications (for example, antipsychotics) are overprescribed. [17][18][19] Practice characteristics such as small list size, low level of socioeconomic deprivation, 20 and a large number of GPs 21 have also been associated with better quality of care for people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Compared with people living in the community, those living in care homes receive poorer care for conditions like heart disease and diabetes, and potentially harmful medications (for example, antipsychotics) are overprescribed. [17][18][19] Practice characteristics such as small list size, low level of socioeconomic deprivation, 20 and a large number of GPs 21 have also been associated with better quality of care for people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was potentially confounded by an increased prevalence of Type 2 diabetes among the people with diabetes from more deprived groups [4]. Another study found that deprivation scores did not predict the quality of care for diabetes, as measured by a complex score encompassing a wide range of process of care measures and intermediate outcomes [16].…”
mentioning
confidence: 99%
“…The survey questionnaire was based on a questionnaire previously used to investigate the quality of care among general practices in England (Campbell, Hann et al 2001), modified to be applicable for prisons by the primary care research interest group of the national Prison Health Research Network. The questionnaire gathered information about the number and types of primary healthcare staff serving prisons and the organisation of care for five common chronic diseases -diabetes, heart disease, asthma, hepatitis and anxiety/depression -and was piloted for acceptability and clarity by healthcare managers at two prisons.…”
Section: Methodsmentioning
confidence: 99%